Effective Teaching and Assessment Tools According to Gen-Z Learners: A Survey Based Study in Physics Education in Nagpur India - Bhakti Rajvaidya; Arsala Zamir Khan (Jurnal Pendidikan Fisika Indonesia, 2026)
This paper presents methodologies derived from a comprehensive survey of students studying at different levels of the education system, as well as of educators in Physics. The survey aimed to understand Generation Z's expectations from education systems and integrate their perspectives into effective teaching and assessment strategies. Key findings reveal the need for innovative approaches to enhance cognitive learning. The paper also aims to offer a list of pedagogies in accordance with Bloom’s taxonomy levels. These strategies prioritize student-centered learning, interactive engagement, and personalized feedback. By incorporating Generation Z's perceptions, educators can foster a more inclusive and effective learning environment, ultimately enriching the educational experience for the next generation of students. The survey highlights a strong shift toward competency-based, skill-oriented learning in line with the National Education Policy and global trends. Students increasingly value application and problem-solving over rote memorization, resonating with Bloom’s revised taxonomy. This underscores the need for formative, competency-based assessments aligned with real-world skills. While traditional classroom note-taking remains important, diverse and flexible learning resources are equally essential to meet varied learning preferences. The findings discussed in the paper offer valuable insights for educators seeking to modernize teaching practices and improve student outcomes.